Extraction and total phenolic content from mistletoe on oil palm (Ficus heteropleura Blume) leaves and evaluation of their antibacterial and antioxidant activities. - Fhadilla Sahara; Fitra Perdana; Rahmiwati Hilma (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2026)
Ficus heteropleura Blume, commonly known as mistletoe, is a semi-parasitic plant frequently found on oil palm plants. This study aimed to evaluate the secondary metabolite content, total phenolic concentration, and the antibacterial and antioxidant activities of the ethanol extract of Ficus heteropleura leaves. Extraction was conducted via grade maceration and total phenolic content was determined using the Folin–Ciocalteu method with gallic acid as the standard. Antibacterial activity was tested using the disc diffusion method against Staphylococcus aureus and Escherichia coli, while antioxidant potential was evaluated through the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. Phytochemical screening confirmed the presence of flavonoids, terpenoids, saponins, tannins, and phenolics with a total phenolic content of 25.500 mg GAE/g. The extract exhibited moderate antibacterial activity with inhibition zones ranging from 7.5 to 10.3 mm. The antioxidant activity was classified as very strong with an IC₅₀ value of 0.67 µg/mL, compared to 0.45 µg/mL for ascorbic acid.